(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Shakespeare’s Othello tragedy is a more realistic tragedy than the playwright’s other works. It gives a realistic picture of the government of that time and the way of life of its citizens, the pure love of two people and human feelings. Just as each nation has its own way of life and customs, so do its realities. Giving an alternative version of the realities in translation is a bit of a challenge. This article is devoted to the issue of realities in the Uzbek language translations of Shakespeare’s tragedy “Othello”. In this article, we will look at examples of how well-preserved words or phrases in the language of a nation in literary translation are preserved in the translated texts.